2004
DOI: 10.1539/joh.46.1
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure Associated with Reproductive Dysfunction

Abstract: Occupational Exposure Associated with R e p r o d u c t i v e D y s f u n c t i o n : S u n i l K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 134 publications
5
121
1
1
Order By: Relevance
“…These findings are in line with previous reports [14,44] in which individuals that were regularly exposed to carbamates and endosulfan reported reproductive and erectile dysfunction. In addition, Burnett [45] in his review reports increased erectile dysfunction and loss of libido in men exposed to a variety pesticides [46,47].…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in line with previous reports [14,44] in which individuals that were regularly exposed to carbamates and endosulfan reported reproductive and erectile dysfunction. In addition, Burnett [45] in his review reports increased erectile dysfunction and loss of libido in men exposed to a variety pesticides [46,47].…”
Section: Discussionsupporting
confidence: 94%
“…However, the knowledge existing today regarding the influence of chemical, physical and emotional factors on male fertility is limited. Moreover, in recent decades, the industrial world has become inundated with an ever-increasing number of chemical and physical agents whose toxicity in general, and toxicity on the male reproductive system, is very little known [10][11][12]. Therefore, the objective of this study was to examine the association between male infertility and certain occupational exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these compounds have been recognized for their mutagenic, carcinogenic and teratogenic potential 1,2) . Many of these compounds are also known for their neurotoxic 3) , reproductive and endocrine disruptive effects 4,5) . Epidemiological studies as summarized by NIOSH 3) have shown significant increase in neurobehavioral effects in workers chronically exposed to organic solvents.…”
Section: Introductionmentioning
confidence: 99%